The Nigerian Quranic exegesis methodology: A comparative study between Radd al-Adhan Ila Ma‘Ani al- Qur’an by Abu Bakr Mahmud Jumi and Diya’ al-Ta’wil Fi Ma‘Ani al-Tanzil by Abdullah bin Fudy / Ibrahim Mohammed Fadul - Ibrahim , Mohammed Fadul (2018)
This research aims to compare the approaches of two books of Tafsīr namely, Radd al-Adhhān ilā Maʿānī al-Qurʾān by Abī Bakr Maḥmūd Jumī and Diyā al-Taʾwīl fī Maʿānī al-Tanzīl by Abī ʿAbd Allah b. Al-Fudī. The problem statement of this research is that the approach of these two scholars in their previous books is not identified, that is why there is a huge need to uncover, identify and highlight the features of each approach through the mentioned books, so they reader can easily benefit from them. This study explores not only the approach of two great Nigerian scholars by comparing their ways in interpreting the Qurʾān by identifying their similarities and differences, but highlighting their effective contribution to the current issues of the Ummah. This research used the inductive, descriptive, analytical, and comparative approaches. The findig of this research shows that both scholars were concerned with the educational and social reform, which is the Qurʾān’s mission. In addition, there is some differences in their approach in terms of dealing with Quranic texts like the excessive reliance on the Tafsīr bi al-Maʾthūr and Tafsīr bi al-Raʾy, and a positive impact on Nigerian society.